2008
DOI: 10.1097/ede.0b013e318176b8ad
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D and Subsequent Occurrence of Type 2 Diabetes

Abstract: The results support the hypothesis that high vitamin D status provides protection against type 2 diabetes. Residual confounding may contribute to this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
221
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(243 citation statements)
references
References 28 publications
16
221
3
3
Order By: Relevance
“…15 Recently, Anoop Shankar et al 16 studied the relationship between serum 25-hydroxyvitamin D levels and prediabetes in an American population, using data from NHANES III. The group with prediabetes comprised 42.9% females versus 55.6% in the non-prediabetes group.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, Anoop Shankar et al 16 studied the relationship between serum 25-hydroxyvitamin D levels and prediabetes in an American population, using data from NHANES III. The group with prediabetes comprised 42.9% females versus 55.6% in the non-prediabetes group.…”
Section: Discussionmentioning
confidence: 99%
“…The level of education was classified into three categories based on the years of education. Venous blood samples were taken, and the sera were kept frozen at -20°C until 2003, when the serum 25-hydroxyvitamin D concentrations were determined using the radioimmunoassay (RIA, DiaSorin, MI) [22].…”
Section: Measurements and Definition Of Determinantsmentioning
confidence: 99%
“…However, some studies assessed only dietary vitamin D intake [6,7], which does not include the major non-dietary component of vitamin D from sun exposure. Other studies measured circulating 25 (OH)D, the best indicator of vitamin D status [8], but had small sample sizes or a limited number of cases [9][10][11]. A recent study reported no association between 25(OH)D and risk of diabetes among older women [12].…”
Section: Introductionmentioning
confidence: 99%